2007
DOI: 10.1080/14622200701705027
|View full text |Cite|
|
Sign up to set email alerts
|

Bupropion Efficacy for Smoking Cessation is Influenced by the DRD2 Taq1A Polymorphism: Analysis of Pooled Data from two Clinical Trials

Abstract: We analyzed pooled data from two comparable randomized placebo-controlled clinical trials of bupropion pharmacotherapy for smoking cessation for which data on DRD2 Taq1A genotype were available. A total of 722 smokers across the two trials were randomized to 10 weeks of sustained-release bupropion hydrochloride or placebo. General estimating equation analysis demonstrated a significant gene x drug interaction (B = 0.87, SE = 0.34, p = .009). Smokers with the A2/A2 genotype using bupropion were more than three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 43 publications
5
64
1
Order By: Relevance
“…The most robust fi ndings associated with this genetic variant are pharmacogenetic. Specifically, the A1 genotype has been reported to be linked with better NRT treatment outcome (e.g., Yudkin et al, 2004 ) while the A2/ A2 carriers are repeatedly found to be more responsive to antidepressants (Cinciripini et al;David, Strong, et al, 2007 ). Moreover, some studies suggest that effects of TaqIA Genotype × Treatment interactions on smoking cessation may be modulated by factors such as sex (Yudkin et al) and craving .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most robust fi ndings associated with this genetic variant are pharmacogenetic. Specifically, the A1 genotype has been reported to be linked with better NRT treatment outcome (e.g., Yudkin et al, 2004 ) while the A2/ A2 carriers are repeatedly found to be more responsive to antidepressants (Cinciripini et al;David, Strong, et al, 2007 ). Moreover, some studies suggest that effects of TaqIA Genotype × Treatment interactions on smoking cessation may be modulated by factors such as sex (Yudkin et al) and craving .…”
Section: Introductionmentioning
confidence: 99%
“…Specifi cally, it is conceivable that counselors and other mental health professionals can use the information to optimize strategies to help these smokers improve their cognitive-behavioral skills to cope with craving, especially in the face of poor cognitive performance and negative affect symptoms. In light of clinical evidence that A1 carriers benefit less from antidepressants for smoking cessation ( Cinciripini et al, 2004 ;David, Strong, et al, 2007 ;David et al, 2003 ), exploring alternative or tailored pharmacological and behavioral interventions for these individuals is warranted.…”
Section: Implications For Smoking Cessation Interventionsmentioning
confidence: 99%
“…41 The CYP2B6 cytochrome metabolizes bupropion, and it has recently been shown that the homozygous T allele (T/T) or heterozygous C and T allele (C/T) at position 1459 of CYP2B6 (rs3211371) are associated with higher odds of abstinence from smoking in people who are also carriers of the DRD2-Taq1 A2/A2 (rs1800497) genotype. 42 Moreover, the common allele with a G-to-T substitution at nucleotide 516 (516G>T; rs3745274) is associated with lower expression via aberrant splicing events, 43 and the amino acid substitution of leucine to phehenylalanine at position 264 (Leu264Phe) has been reported to have functional consequences on CYP2B6 activity. 44 This is quite interesting because CYP2B6 and CYP3A4 are the main isoforms involved in metabolizing methadone and sibutramine (CYP2B6 only), and it is thought that part of the individual response to these drugs depends on genetic variants of these cytochromes.…”
Section: Cytochrome P450mentioning
confidence: 99%
“…286,287 Some evidence addresses a role of D2 receptors in the pharmacodynamics of smoking cessation. 42,288 A functional polymorphism in the DRD2 gene, which causes a structural change from serine to cysteine at codon 311 (Ser311Cys; rs1801028), 289 showed no significant influence on antidepressant response in some studies. 223,290,291 The DRD4 gene has also been investigated as a possible candidate gene in the pharmacogenetics of the antidepressant response.…”
Section: Dopamine Receptorsmentioning
confidence: 99%
“…Several biologically plausible candidate gene variants have been identified within this genomic region in genetic association studies of nicotine dependence and smoking cessation (Abrous et al, 2002;Breen et al, 1999;Jonsson et al, 1996;Jonsson et al, 1999;Katoh & Katoh;Noble, Blum, Ritchie, Montgomery, & Sheridan, 1991;Noble, Gottschalk, Fallon, Ritchie, & Wu, 1997;Yang et al, 2007Yang et al, , 2008. For example, functional genetic variants in the DRD2 gene (i.e., rs6277 "exon [S] [C957T]"); rs1799732 "promoter (ins/del)" and ANKK1 gene (i.e., rs1800497 "TaqIA") have been associated with efficacy of NRT and bupropion for smoking cessation David, Strong, et al, 2007;Johnstone et al, 2004;Lerman et al, 2003Lerman et al, , 2006Swan et al, 2005Swan et al, , 2007Yudkin et al, 2004). Of the genetic variants within this cluster, the TaqIA variant is the most widely studied for association with smoking behavior.…”
Section: Introductionmentioning
confidence: 99%